The Library in the 21st Century: Transformation in Romania - Radu Alexandru Tonca (Athens Journal of Architecture, 2016)
This research paper aims to analyze Romanian contemporary Libraries in their relationship with small communities, highlighting the impact that institutions may have in their cultural and social sphere and to theorize the concept of the "Open Library" and all that means transformation in the last decades, both in terms of form and their role in the community. The central idea of this paper is to dissect the relationship between the Library and the readers/community and to discuss or discover various ways through which one can achieve and "open" fruitful attitude and involvement. This discussion analyzes how the contextual sphere of the reading process itself has changed over time and we speak of a triad: reading-book-readers, a relational triangle that forms a foundation for the Library. Analyzing the relationship between the Community and the Library is important in the context of digitization and virtualization of books and information, as one must find solutions for a healthy relationship, collaboration and education. When we speak of the library of the XXI century, we think of the image of a glass box, perfectly transparent, very accessible located in the heart of the city/neighborhood. Today, its role goes far beyond the one it had only one or two centuries ago and is no longer enough for the library to be open and to wait for the reader, it must be a catalyst for both the cultural life of the community and the development of each of its members.